Awareness on three-dimensional printing of orthodontic appliances among dental students - Jayadharani Chandran; Nivethigaa Balakrishnan; Swapna Sreenivasagan (Wolters Kluwer Medknow Publications, 2022)
The aim of the study was to evaluate the knowledge and awareness regarding the use of three-dimensional (3D)-printed appliances used in orthodontics among students pursuing dentistry. The distribution of the questionnaire was done using an online Google Forms link to about 100 dental students. The questionnaire compromised questions that were designed for assessing the various findings and knowledge of update, and finally, questions related to facts on various 3D-printing appliances. Among the total population, 58% of the population are aware of 3D printing used for various dental applications, whereas 42% of the population are not aware of the same. Among the total population, 58% of the population are aware of 3D printing used in dentistry, whereas 42% of the population are not aware of 3D printing used in dentistry. Inside the limits of the review, it very well may be inferred that 3D-printed machines have a rising use in the majority of the dental fields and understudies chasing after dentistry know about it. The knowledge about the basic and fundamental working and the usage of such appliances is developing among undergraduate students. Further continuing education programs can be provided to improve the same.